The retail distribution review: Retail financial services; regulation; financial advice market review. Issue 2 (9th May 2016) - Ring, Patrick
Abstract : Purpose: The purpose of this paper is to review the effect of reforms to the UK's retail advice sector as a result of the Retail Distribution Review (RDR). Design/methodology/approach: The paper takes the form of a review of the RDR in the context of the Financial Advice Market Review (FAMR). Findings: There is a lack of clarity, experienced by both consumers and financial advisers, concerning the nature of "advice". This results from the use of an array of regulatory and non-regulatory terms. Whilst enhancing professionalisation and reducing commission bias, the RDR is failing to address the needs of many financial consumers – identified by many as an "advice gap". It is argued that the focus of the RDR, and previous reforms, on addressing market failures may be misplaced. Practical implications: The paper provides an analysis designed to help in the process of developing a retail advice sector that meets the needs of consumers, in the context policy reforms placing more emphasis on the responsibilities of individuals for financial planning. Social implications: The study has the potential of better outcomes for consumers and reputational returns for the financial services sector. Originality/value: This paper is a review of the current regulatory issues facing financial advisers and retail consumers in the context of the RDR and FAMR.